Indications and added value of videourodynamics in men with spinal cord injury - Marc Françot; Chloé Lefevre; Bénédicte Reiss; Marc Lefort; Georges Karam; Jerome Rigaud; Loic Le Normand; Alain Ruffion; Brigitte Perrouin‐Verbe; Marie‐Aimee Perrouin‐Verbe (BJUI Compass)
Abstract Purpose The primary aim of this study was to evaluate the indications and additional information provided by videourodynamic study (VUDS) over urodynamic studies (UDS) in men with spinal cord injury (SCI) and neurogenic lower urinary tract dysfunction (NLUTD). The secondary aim was to determine the added value of VUDS and its impact on bladder management. Materials and Methods Single‐centre retrospective study of all men with SCI who underwent VUDS between 2011 and 2021. Participant characteristics, clinical data and indications for UDS and VUDS as well as bladder management were recorded. The added value of VUDS was defined as additional information not provided by standard UDS that impacted on bladder management (choice of voiding mode, surgical indication or type of surgery). Results Eighty‐eight men with a median age of 52 years were included. In 20 men who were unable to perform self‐catheterisation, the VUDS clarified the nature and extent of the obstruction and enabled targeted surgery to achieve reflex bladder emptying in all of them. VUDS also clarified the type and level of obstruction in 28 patients, enabling targeted surgery in 24. In 11 men, VUDS was performed as part of the preoperative assessment for a Brindley procedure or after this operation if a complication occurred during follow‐up to confirm the need for further surgery or to target surgical revision. Overall, VUDS had added value in 59 patients (67%). Conclusions VUDS had added value over UDS in specific situations; the additional information provided impacted on bladder management in men with SCI and NLUTD.